THE ROLE OF INDONESIAN YOUNG DIASPORA IN CULTURAL DIPLOMACY FOR STRENGTHENING INTERNATIONAL RELATIONS - Efendi, Adellia Syafira; Handayani, Trisakti; Wibowo, Arif Prasetyo (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the role of Indonesian youth living abroad as cultural agents in the practice of cultural diplomacy, especially in maintaining the sustainability of Indonesian cultural values, facing the challenge of cultural identity in the destination country, and utilizing cultural diplomacy as a strategy to strengthen sustainable international networks and cooperation. This study uses a qualitative approach with a case study method on the Indonesian Student Association (PPI) organization located in Japan, South Korea, Germany, and Austria The results of the study show that Indonesian youth living abroad actively carry out cultural diplomacy through various cultural, academic, social, and community activities that are adapted to the socio-cultural context in the destination country. Activities such as cultural festivals, art exhibitions, traditional performances, academic forums, and the use of digital media have proven to play an important role in building cultural attraction and strengthening Indonesia's positive image at the international level. In addition, this study found that cultural diplomacy carried out by diaspora youth not only functions as a means of cultural representation, but also as a strategic mechanism in building international networks based on trust, exchange of ideas, and cross-cultural interaction. These findings confirm that Indonesian diaspora youth have a strategic position as non-state actors in supporting the strengthening of Indonesian cultural diplomacy in the era of globalization, as well as contributing to strengthening international relations through a sustainable soft power approach.